Black history : a retrospective. ([Golden Valley, Minn.] : Mill Creek Entertainment, 2009)
Features the life, culture, and accomplishments of some of the most influential African Americans in history from the United States. From the oppression and hardship during the time of the Civil War to civil rights movements that paved the way to this country's first African-American president. A definitive retrospective of Black history in America.
Documentary./ Title from container./ "40 documentary collection."/ Audience: MPAA rating: Not rated.
Keywords: African Americans -- History; African Americans -- Biography